2008
DOI: 10.1577/m05-190.1
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics of Lake Superior Brook Trout: Issues, Questions, and Directions

Abstract: Parallel efforts by several genetic research groups have tackled common themes relating to management concerns about and recent rehabilitation opportunities for coaster brook trout Salvelinus fontinalis in Lake Superior. The questions that have been addressed include the evolutionary and genetic status of coaster brook trout, the degree of relatedness among coaster populations and their relationship to riverine tributary brook trout populations, and the role and effectiveness of stocking in maintaining and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Genetically distinct ecotypes of fish are often documented between migratory and resident life histories (Lin, Quinn, Hilborn, & Hauser, ; Pearse et al., ; Taylor, ), but only sparsely so in brown trout, possibly in part as a result of sample bias (Hindar, Jonsson, Ryman, & Stahl, ; Krueger & May, ; Skaala & Naevdal, ). As in the present investigation, an ecotype signal may be less pronounced than genetic differentiation among geographically defined populations, and studies may give ambiguous results, often related to the different populations studied (Bernatchez et al., ; Docker & Heath, ; Heath, Bettles, Jamieson, Stasiak, & Docker, ; Marin et al., ; Olsen, Wuttig, Fleming, Kretschmer, & Wenburg, ; Wilson et al., ). Sympatric populations with different life history strategies are typically more similar to each other, than to geographically separated populations (Aykanat et al., ; Bernatchez et al., ; Docker & Heath, ; Hindar et al., ; Narum, Contor, Talbot, & Powell, ; Perreault‐Payette et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…Genetically distinct ecotypes of fish are often documented between migratory and resident life histories (Lin, Quinn, Hilborn, & Hauser, ; Pearse et al., ; Taylor, ), but only sparsely so in brown trout, possibly in part as a result of sample bias (Hindar, Jonsson, Ryman, & Stahl, ; Krueger & May, ; Skaala & Naevdal, ). As in the present investigation, an ecotype signal may be less pronounced than genetic differentiation among geographically defined populations, and studies may give ambiguous results, often related to the different populations studied (Bernatchez et al., ; Docker & Heath, ; Heath, Bettles, Jamieson, Stasiak, & Docker, ; Marin et al., ; Olsen, Wuttig, Fleming, Kretschmer, & Wenburg, ; Wilson et al., ). Sympatric populations with different life history strategies are typically more similar to each other, than to geographically separated populations (Aykanat et al., ; Bernatchez et al., ; Docker & Heath, ; Hindar et al., ; Narum, Contor, Talbot, & Powell, ; Perreault‐Payette et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…The four strains of brook trout chosen, based on their life history strategies and availability, were two lacustrine coasters (NIP: Lake Nipigon, Ontario, Canada; TBH: Isle Royale, Michigan, USA), one adfluvial coaster (SIS: Siskiwit River, Isle Royale, Michigan, USA), and one stream-resident strain (IRV: Iron River, Michigan, USA). Recent studies have shown that there is genetic diversity within brook trout populations around Lake Superior, including the strains used in our study (Wilson et al 2008;Burnham-Curtis 2001). All strains used in this study are recognized as genetically distinct populations in the wild, and derived hatchery stocks are similarly distinct.…”
Section: Fish and Experimental Systemmentioning
confidence: 92%
“…Analyses of historical genetic data can provide information useful for evaluating the impacts of anthropogenic effects and generating population genetic baselines by which to measure genetic change and define management goals (Vähä et al 2008;Wilson et al 2008;. For this study, we developed historical genetic baselines for the Ohio River strain (museum specimens) and Great Lakes strain (contemporary Lake Erie basin) of Walleyes to compare against contemporary Ohio River populations.…”
Section: Temporal Genetic Assessmentmentioning
confidence: 99%